Nanoscale Technology for Advanced Lithium Batteries - Osaka, Tetsuya; Ogumi, Zempachi; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
The unfortunate and serious accident at the nuclear power plants in Fukushima, Japan caused by the earthquake and tsunami in March 2011 left Japan with a serious blow. Japan was deprived of electric power. This problem further accelerated the introduction of renewable energies. This book surveys the new materials and technologies needed to welcome the next generation of energy conversion and storage devices, such as lithium secondary batteries on the basis of nanotechnology. Most of the contributors for this book are from institutions researching lithium batteries. This book provides an overview of nanotechnology for lithium batteries from basic to applied research in selected high technology areas. The book especially focuses on near-term and future advances in these fields.
Energy systems for green community -- Positive electrodes of Nano-scale for lithium ion batteries (focusing on nan-size effects) -- Nano-aspects of Advanced Positive Electrodes for Lithium Ion Batteries -- Nano-aspects of Carbon Negative Electrodes for Li-ion Batteries -- Advanced negative electrodes of Nano-scale for Li-ion Batteries -- Polymer and Ionic Liquid Electrolytes for Advanced Lithium Batteries -- Development of glass-based solid electrolytes for lithium ion batteries -- 3DOM Structure for Battery Electrode and Electrolyte -- DC methods for Battery evaluation -- Characterization of neighbor atoms (X-ray absorption) (Covering wide area of XAFS and XANES) -- AC methods for Battery evaluation -- NMR Study of Lithium-Ion Battery -- Nano-aspect of Vibration Spectra Methods in Lithium-ion Batteries -- Nano-aspects of Metal Air Batteries -- Lithium/Air Battery -- Nano-Aspects of Lithium/Sulfur Batteries -- Possibility and Prospect for Future Energy Storages.
Keywords: Chemistry; Electrochemistry; Electric power production; Nanotechnology; Chemistry; Electrochemistry; Nanotechnology; Energy Technology; Electronic books